The significance of smoking as a risk factor for the disorder of the obstructive pulmonary pattern in the patients with systemic sclerosis - Stefanović Nešković, Jelena; Petronijević, Milan; Ristić, Andjelka; Djurović, Branka; Stević-Carević, Silvija; Nešković, Branimir (Vojnosanitetski pregled, 2021)
Background/Aim. Systemic sclerosis (SSc) is a chronic systemic disease of the connective tissue. It is characterized by diffuse microangiopathy, increased activity and creating deposits of collagen in the skin and internal organs. Involvement of the lung function disturbances in SSc is a bad prognostic sign. The aim of our study was to investigate the association between smoking habits and lung function disorder in the SSc patients. Methods. The testing was conducted at the Clinic for Rheumatology and Immunology of the Military Medical Academy in 2016. In this study, we included 42 patients with the newly diagnosed SSc and the patients whose disease had been diagnosed earlier. Results. The patients were classified according to the smoking habits, 14 (33.3%) patients were nonsmokers, while 28 (66.7%) patients were current (23 patients) or ex-smokers (5 patients). We found no significant differences in examined parameters among smokers and nonsmokers. In addition, distribution of the patients with the obstructive pulmonary pattern revealed by spirometry was uniform between smokers and nonsmokers. The concentrations of C reactive protein (CRP) were significantly higher in the SSc patients with the obstructive pulmonary pattern. The patients with the obstructive pattern on spirometry had significantly lower values of forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), FEV1/FVC ratio, diffusing lung capacity for carbon monoxide (DLCO) and FVC/DLCO ratio. Conclusion. In our study, we concluded that in the SSc patients with the obstructive pulmonary pattern revealed by spirometry, there were no significant differences between smokers and non-smokers. CRP is a significant predictor of the lung involvement existence in the SSc patients.
Keywords: scleroderma, systemic; lung diseases, obstructive; risk factors; smoking.